Função sexual de mulheres diagnosticadas com lesão de colo uterino - Silva, Cassiana Roncada Bardo da; Michelon, Pablo Heitor Gubert (My University, 2019)
Introduction: Cervical cancer is the third most frequent tumor in the female population, which, HPV infection is necessary for the onset of cervical intraepithelial neoplasia (CIN). Most infections heal spontaneously, but up to 20% of HPV infections persist, resulting in squamous intraepithelial lesions, with possible negative sexual repercussions related to the disease and to its treatments. Methodology: This is an observational epidemiological study of the cross-sectional type, with an analysis of the medical records of patients participating in a previous study, in which the sociodemographic and obstetrical gynecological data were collected and the FSFI questionnaire was used. Results: Of a total of 279 participants in the study, 29 took part in this study according to the inclusion criteria. The mean age was 37.51 ± 11.34 and the predominance was senior high school education, accounting for 55.2% of the population. The FSFI scores presented a mean of 23.74 (± 7.99), and the most affected domains were arousal (3.50 ± 1.27), lubrication (4.06 ± 1.97) and pain (4, 10 ± 1.20). Conclusion: The results of the present study show a significant difference regarding the presence of sexual dysfunction in patients who had not undergone surgical treatment compared to those who had. We emphasize the importance of further studies covering female sexual dysfunction and cervical lesions, and the need to observe the influence of the specialties involved in the treatment on the recovery of these patients. [resumo fornecido pelos autores]
Sexual function of women diagnosed with cervical intraepithelial neoplasia
Introdução: O câncer de colo de útero é o terceiro tumor mais frequente na população feminina, sendo que, a infecção pelo vírus HPV é necessária para o surgimento da neoplasia intraepitelial cervical (NIC). A maioria das infecções se cura espontaneamente, mas até 20% das infecções por HPV persistem, gerando lesões intra-epiteliais escamosas, com possíveis repercussões sexuais negativas relacionadas à própria doença e também a seus tratamentos. Metodologia: Trata-se de um estudo epidemiológico observacional do tipo transversal, com análise de prontuários de pacientes participantes de uma pesquisa prévia, onde foram coletados dados sócio demográficos e gineco obstétricos e aplicação do questionário FSFI, sendo estes dados utilizados para análise neste estudo. Resultados: De um total de 279 participantes da pesquisa, 29 fizeram parte deste estudo segundo os critérios de inclusão. A média de idade expressouse em 37,51±11,34 e a escolaridade predominante foi o ensino médio, contando com 55,2% da população. Os escores do FSFI apresentaram uma média de 23,74 (±7,99), e os domínios mais prejudicados foram excitação (3,50±1,27), lubrificação (4,06±1,97) e dor (4,10±1,20). Conclusão: Os resultados do presente estudo evidenciam uma diferença expressiva quanto à presença de disfunção sexual das pacientes que não haviam realizado tratamento cirúrgico em relação às que haviam realizado. Salientamos a importância da realização de mais estudos abrangendo a disfunção sexual feminina e as lesões de colo uterino, e a necessidade de observar a influência das especialidades envolvidas no tratamento na recuperação dessas pacientes. [resumo fornecido pelos autores]
Keywords: Mulheres - Doenças; Sexo; Colo uterino; Fisioterapia; Papilomavírus